Strategi Pembelajaran Sosial Emosional Dalam Pencegahan Perundungan, Bullying Pada Kurikulum Merdeka - Kusumardi, Adi (LENTERNAL: Learning and Teaching Journal, 2024)
The research is based on the high levels of violence and bullying in the educational environment. To implement the Social Emotional Learning (SEL) curriculum professionally, effectively, as well as to raise awareness about the consistent application of SEL every day, teachers need adequate training. Writing this article aims to raise awareness about how teachers understand and convey SEL as part of the curriculum in prevention of negotiation and bullying. Helping educational units and teachers in better implementation of SEL teaching so that it can prevent the growth of negotiations and bulyying in the school environment. This type of research is qualitative research with discryptive methods and using phenomenological approaches. Data collection methods used are interviews, observations and documentation. Then the data is analyzed with the data reduction pattern, the presentation of the data continues with the drawing of conclusions. Data sampling techniques are performed using purposive samplings which are continued with data validity testing in the form of triangulation. This study was conducted on the participants of the Third Candidate Master Movement (CGP) of the 9th Army of the Western Frame. Research findings show that strategies to address the growing problem of counseling and bullying cases include: (a) creating a SEL-based teaching module so that teachers have readings or references after training; (b) providing training through CGP or other forms and examples that facilitate application understanding; (c) developing SEL skills through practical practice to enhance teacher skills.